Economic valuation of native forest affected by the North American beaver (Castor canadensis) in Tierra del Fuego - Soto Simeone, Aracely; Soza-Amigo, Sergio (Bosque (Valdivia), 2017)
How much is the economic value of native forest affected by the North American beaver in Tierra del Fuego? That was the question which led to determine the value given by society to forest resources affected by the introduction of the North American (or Canadian) beaver in conservation areas in Tierra del Fuego Province. The contingent valuation technique was applied and 396 persons of the economically active population from Punta Arenas and Porvenir were examined. This research found that 18.7 % of the value placed on these resources is an option value, 48.8 % corresponds to a heritage value, 17.1 % falls on the existence value and 15.5 % is attributed to their direct and indirect use values; thus, bringing its total valuation to $ 4,864,507.534 (Chilean pesos, 2011) per year.